Efektifitas Pelaksanaan Peraturan Daerah Kabupaten Badung Nomor 2 Tahun 2016 Tentang Sistem Online Pajak Daerah - I Gusti Ayu Mas Yuni; I Gusti Bagus Suryawan; Luh Putu Suryani (Warmadewa Press, 2020)
The Regional Revenue Agency / Pasedahan Agung Badung Regency is a regional apparatus organization that has the main objective and function of managing regional revenue as a source of regional financing in implementing regional development. This study aims to analyze the implementation procedures and determine the effectiveness of the implementation of the Badung Regency Regulation Number 2 of 2016 concerning the Local Tax Online System. This study uses an empirical method. There are 2 forms of data used, namely primary and secondary, namely collected through interviews. The results showed that the procedures for implementing the online system of local taxes for taxpayers to report their taxes through the Revenue Agency web and the installation of recording devices for monitoring business transactions on taxpayers. The implementation of the Local Tax Online System can be said to be effective as seen from the increase in online tax reporting and the increase in the installation of business transaction monitoring tools for taxpayers and the increase in PAD Taxes. The juridical and non-juridical constraints are the taxpayers who refuse to install a recording device for monitoring taxpayers' business transactions. Therefore, through this research, the Regional Revenue / Pasedahan Agency is expected to increase the socialization of understanding and reinforce the sanctions in the Badung Regency Regional Regulation Number 2 of 2016 concerning the Online Regional Tax System